'I know it's not normal but it's normal to me, and that's all that matters': experiences of young adults conceived through egg donation, sperm donation, and surrogacy. Issue 5 (15th March 2023) - Jadva, V; Jones, C; Hall, P; Imrie, S; Golombok, S
Abstract: STUDY QUESTION: What are thoughts and feelings of young adults born following egg donation, sperm donation, and surrogacy? SUMMARY ANSWER: Young adults felt either unconcerned or positive about the method of their conception. WHAT IS KNOWN ALREADY: Much of what we know about adults born to heterosexual couples following anonymous donation has come from samples of donor conceived people who had found out about their origins during adulthood. There have been no studies of how young adults born through surrogacy feel about their conception and towards their surrogate. STUDY DESIGN, SIZE, DURATION: Thirty-five young adults were interviewed as part of the seventh phase of a larger multi-method, multi-informant longitudinal study of assisted conception families in the UK. Adults were conceived using either egg donation, sperm donation, gestational surrogacy, or genetic surrogacy and were raised in households headed by heterosexual couples. PARTICIPANTS/MATERIALS, SETTING, METHODS: Participants had a mean age of 20 years and were born following traditional surrogacy (n = 10), gestational surrogacy (n = 5), egg donation (n = 11), or sperm donation (n = 9). All young adults born following sperm donation and most (n = 10) born from egg donation had an anonymous donor. In all surrogacy arrangements, the parents had met the surrogate prior to treatment. The majority of young adults were told about their conception by the age of 4 years. Participants were interviewed over the internet using a semi-structured interview. Interviews were transcribed verbatim and analysed using qualitative content analysis to understand young adults' thoughts and experiences related to their conception and whether they were interested in meeting their donor or surrogate. MAIN RESULTS AND THE ROLE OF CHANCE: Fourteen (40%) young adults felt their conception made them feel special or unique, with the remainder feeling either neutral or unconcerned (n = 21, 60%). A higher proportion of young adults conceived using egg donation (n = 8, 73%) felt unique/special compared to young adults born following sperm donation and surrogacy. For 10 of the young adults, their feelings about their conception had changed over time, with most becoming more positive (n = 9, 26%). For most young adults (n = 22, 63%), conception was rarely or infrequently discussed with others. However, when it was, these conversations were largely conducted with ease. Most (n = 25, 71%) did not know other individuals born through the same method of conception as themselves, and the vast majority (n = 34, 97%) were not members of any support groups. For the 25 young adults not in contact with their donor or surrogate, 11 wished to meet them, 8 did not want to have contact, and 6 were unsure. Young adults in contact with their donor or surrogate had varying levels of closeness to them. Only one young adult had searched for the identity of their donor. LIMITATIONS, REASONS FOR CAUTION: Of the 47 young adults invited to participate in the present study, 35 agreed to take part resulting in a response rate of 74%. It is therefore not known how those who did not take part felt about their conception. Given that the families reported here had been taking part in this longitudinal study from when the target child was aged 1 year, they may have been more likely to discuss the child's conception than other families. The study also utilized self-report measures, which may have been prone to social desirability, with donor conceived young adults wanting to present their experiences in a positive light. WIDER IMPLICATIONS OF THE FINDINGS: The findings suggest that young adults born through surrogacy and donor conception do not feel negatively about their birth and this may be a consequence of the young age at which they found out about their conception. Although some young adults said they wished to meet their donor, this did not necessarily mean they were actively searching for them. STUDY FUNDING/COMPETING INTEREST(S): The study was funded by the Wellcome Trust [grant number 208013/Z/17/Z]. The authors have no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: N/A.